2019
DOI: 10.3390/app9132755
|View full text |Cite
|
Sign up to set email alerts
|

Geometry of the Vocal Tract and Properties of Phonation near Threshold: Calculations and Measurements

Abstract: In voice research, analytically-based models are efficient tools to investigate the basic physical mechanisms of phonation. Calculations based on lumped element models describe the effects of the air in the vocal tract upon threshold pressure (Pth) by its inertance. The latter depends on the geometrical boundary conditions prescribed by the vocal tract length (directly) and its cross-sectional area (inversely). Using Titze’s surface wave model (SWM) to account for the properties of the vocal folds, the influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
(89 reference statements)
2
0
0
Order By: Relevance
“…MLM1, however, lied in these ranges, which will be discussed in more detail in Section 3.5. These higher values of the P sub in synthetic models matched well with many previous studies [31,51,80]. When compared to ex vivo measurements [45][46][47][48]81], the P sub in our models is also higher.…”
Section: General Phonation Parameterssupporting
confidence: 92%
“…MLM1, however, lied in these ranges, which will be discussed in more detail in Section 3.5. These higher values of the P sub in synthetic models matched well with many previous studies [31,51,80]. When compared to ex vivo measurements [45][46][47][48]81], the P sub in our models is also higher.…”
Section: General Phonation Parameterssupporting
confidence: 92%
“…It can be seen that V stays roughly constant for L ≤ 340 mm and decreases monotonically for larger L. The same behavior can be observed in the transglottal pressure P trans = P sub − P supra , where P sub and P supra are the mean pressure values measured by the pressure probes in the sub-and supraglottal channel, respectively. The decrease in V with increasing L is similar to what Fulcher et al [41] found, where they used an analytical surface wave model in combination with validation experiments to predict the phonation threshold pressure as a function of the vocal tract length. They related the decreased threshold pressure to an increase in vocal tract inertance due to the increased length.…”
Section: General Resultssupporting
confidence: 81%